2017
DOI: 10.1016/j.tranon.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30e Functions as a Tumor Suppressor in Cervical Carcinoma Cells through Targeting GALNT7

Abstract: Cervical cancer is the third most common cancer in women worldwide. However, the underlying mechanism of occurrence and development of cervical cancer is obscure. In this study, we observed that miR-30e was downregulated in clinical cervical cancer tissues and cervical cancer cells. Next, overexpression of miR-30e reduced the cervical cancer cell growth through MTT, colony formation, EdU, and Transwell assay in SiHa and Caski cells. Subsequently, UDP-N-acetyl-D-galactosamine: polypeptide N-acetylgalactosaminyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Enzymes affecting metabolism of glycolipids and glycoproteins whose expression levels change in response to HDAC inhibition are grouped according to their affected pathway and whether the protein product is associated with cancer (are in bold) or is the initial step in the biosynthetic pathway (are in italic). References documenting the gene product link to cancer indicated in parenthesesBiosynthetic & other metabolic processesLog2 Fold-changeSymbolGene NameMultiple Pathways −1.26 FUT10 α-(1,3)-fucosyltransferase 10 [46, 47] −1.26 FUT11 α-(1,3)-fucosyltransferase 11 [46, 48, 49] −1.56 B4GALT2 UDP-Gal:β-GlcNAc β-(1,4)-galactosyltransferase 2 [50] 1.07B3GAT2β-(1,3)-glucuronyltransferase 2GlycoproteinEGF Domain −1.04 POGLUT1 Protein O-glucosyltransferase 1 [5053] 1.30 LFNG O-fucosylpeptide 3-β-GlcNAc transferase [50, 54]N & O-Linked Pathways 1.56 B3GNT2 N-acetyllactosaminide β-(1,3)-GlcNAc transferase 2 [50, 55]Complex N-Linked Pathway −1.10 ALG13 UDP-GlcNAc transferase subunit [50] −1.09 ALG10 α-1,2-glucosyltransferase [56] 5.16 MAN1A1 α-Mannosidase, class 1A, member 1 [8, 52] 1.63 MGAT4A α-(1,3)-mannosyl-glycoprotein 4-β-N-acetylglucosaminyltransferase A [50, 56]Complex O-linked Pathway −1.28 GALNT14 Polypeptide GalNAc transferase 14 [8, 57, 58] 1.00 GALNT6 Polypeptide GalNAc transferase 6 [8, 50] −1.08 GALNT7 GalNAc transferase 7 [8, 50, 59, 60] 1.79 GCNT1 β-(1,3)-galactosyl-O-glycosyl-glycoprotein β-1,6-GlcNAc transferase […”
Section: Resultsmentioning
confidence: 99%
“…Enzymes affecting metabolism of glycolipids and glycoproteins whose expression levels change in response to HDAC inhibition are grouped according to their affected pathway and whether the protein product is associated with cancer (are in bold) or is the initial step in the biosynthetic pathway (are in italic). References documenting the gene product link to cancer indicated in parenthesesBiosynthetic & other metabolic processesLog2 Fold-changeSymbolGene NameMultiple Pathways −1.26 FUT10 α-(1,3)-fucosyltransferase 10 [46, 47] −1.26 FUT11 α-(1,3)-fucosyltransferase 11 [46, 48, 49] −1.56 B4GALT2 UDP-Gal:β-GlcNAc β-(1,4)-galactosyltransferase 2 [50] 1.07B3GAT2β-(1,3)-glucuronyltransferase 2GlycoproteinEGF Domain −1.04 POGLUT1 Protein O-glucosyltransferase 1 [5053] 1.30 LFNG O-fucosylpeptide 3-β-GlcNAc transferase [50, 54]N & O-Linked Pathways 1.56 B3GNT2 N-acetyllactosaminide β-(1,3)-GlcNAc transferase 2 [50, 55]Complex N-Linked Pathway −1.10 ALG13 UDP-GlcNAc transferase subunit [50] −1.09 ALG10 α-1,2-glucosyltransferase [56] 5.16 MAN1A1 α-Mannosidase, class 1A, member 1 [8, 52] 1.63 MGAT4A α-(1,3)-mannosyl-glycoprotein 4-β-N-acetylglucosaminyltransferase A [50, 56]Complex O-linked Pathway −1.28 GALNT14 Polypeptide GalNAc transferase 14 [8, 57, 58] 1.00 GALNT6 Polypeptide GalNAc transferase 6 [8, 50] −1.08 GALNT7 GalNAc transferase 7 [8, 50, 59, 60] 1.79 GCNT1 β-(1,3)-galactosyl-O-glycosyl-glycoprotein β-1,6-GlcNAc transferase […”
Section: Resultsmentioning
confidence: 99%
“…MiR-30e regulated GALNT7 transcripts in cervical cancer [ 42 ]. MiR-34a was downregulated in colon cancer specimens compared to normal colonic mucosa [ 43 ]. MiR-30a-5p regulated GALNT7 transcripts in renal cell carcinoma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al have reported that miR-378 is a novel therapeutic strategy in CC (Li, Yang, Wang, Cao, & Yang, 2017). MiR-30e can suppress the proliferation and invasion of CC cells through targeting mRNA and it can be a new therapeutic target for CC in the future (Wu et al, 2017). Wang et al have shown that overexpression of miR-34a-5p prevented proliferation of CC cells and promoted apoptosis of these cells by downregulating Bcl-2 expression (Wang, Xie, & Wang, 2017).…”
Section: Mirnas As Therapeutic Targetsmentioning
confidence: 99%